Electrical and photovoltaic properties of cobalt doped zinc oxide nanofiber/n-silicon diode - Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2010)
Nanofiber Co-doped ZnO (ZnO:Co) film was deposited on n-type silicon substrate at room temperature by using sol-gel method. Scanning electron microscopy results indicate that cobalt doped zinc oxide film has a nanofiber structure. The electrical and photovoltaic properties of the Au/ZnO:Co/n-Si diode were investigated by current-voltage, capacitance-voltage, transient current and steady state photoconductivity measurements. The Au/ZnO:Co/n-Si diode exhibits a photovoltaic behavior with a maximum open circuit voltage V(oc) (0.195 V) and short-circuit current I(sc) (2.63 mu A) values under 100 mW cm(2) illumination intensity and the photoconductivity mechanism of the diode is controlled by the presence of continuous distribution of traps. The interface state density for the diode was determined by conductance method under dark and illumination conditions. The interface state density D(it) and time constant tau values for the diode under dark and 100 mW/cm(2) conditions were found to be 1.26 x 10(10) eV(-1)cm(-2), 6.02 x 10(-5) s and 9.81 x 10(10) eV(-1) cm(-2), 7.35 x 10(-7) s, respectively. The obtained photovoltaic and photocapacitance results indicate that the diode can be used both as a photodiode and photocapacitive sensor for visible light sensor applications. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Semiconductors; Heterojunctions